EVALUATION OF B4C/TI COATING LAYER, INVESTIGATION OF ABRASIVE WEAR BEHAVIORS USING TAGUCHI TECHNIQUE AND RESPONSE SURFACE METHODOLOGY - Gur, Ali Kaya; Ozay, Cetin; Icen, Busra (World Scientific Publ Co Pte Ltd, 2020)
In this study, the surface of AISI 430 stainless steel was alloyed with B4C using the plasma transferred arc welding hardface coating method and the effect of Ti addition was examined. The microstructure of the resultant hardface coating layer was examined through X-ray diffraction (XRD) analyses by using the scanning electron microscopy (SEM). Abrasive wear resistance was analyzed by measuring mass loss according to the L-16 orthogonal array using the Taguchi design method. The smaller the better principle of the Taguchi method was used in graphic evaluations. Additionally, the effect of wear test factors on mass loss was calculated in % by performing the analysis of variance. As a result, the austenite, martensite, M-23(B,C)(6), M-7(B,C)(3), Ti(B,C),Fe-3(C,B), Fe3C, Fe2C and Ti (B,C) phases were detected in the coating layers. The effect of these phases on wear behavior was evaluated. In addition, the optimization of the parameters was obtained with response surface methodology (RSM) based on Taguchi orthogonal experimental design. The results given by the effect parameters required for the developed wear estimation are successful. As a result of the ANOVA analysis, the most effective parameters for wear resistance mass loss were determined as wear distance, applied load and abrasive, respectively. It was observed not to have any effect on wear mass loss of the samples. The most suitable parameter values for the lowest wear values were determined.
Keywords: PTA coating; B4C; Ti; wear; Taguchi; response surface methodology